2019
DOI: 10.1017/cts.2019.366
|View full text |Cite
|
Sign up to set email alerts
|

Addressing community health needs through community engagement research advisory boards

Abstract: Over 80% of CTSA programs have a community advisory board (CAB). Little is known about how research discussed with CABs aligns with community priorities (bidirectionality). This program evaluation assessed researcher presentations from 2014 to 2018 to the CABs linked to our CTSA at all three sites (Minnesota, Arizona, and Florida) for relevance to local community needs identified in 2013 and/or 2016. From content analysis, of 65 presentations total, 41 (63%) addressed ≥1 local health needs (47% Minnesota, 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Stakeholder engagement through CABs is intended to promote transparency of research processes and improve translation of research to practice 92 while helping to shape research so that it better aligns with community priorities. 93 In that way, CAB members who are representative of diverse study populations can help craft recruitment strategies that are most likely to be authentic 94 while helping members of their community understand the risks and benefits of research participation. 95,96 Nationally, CABs have expanded rapidly as standing institutional committees and/or study-specific entities.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholder engagement through CABs is intended to promote transparency of research processes and improve translation of research to practice 92 while helping to shape research so that it better aligns with community priorities. 93 In that way, CAB members who are representative of diverse study populations can help craft recruitment strategies that are most likely to be authentic 94 while helping members of their community understand the risks and benefits of research participation. 95,96 Nationally, CABs have expanded rapidly as standing institutional committees and/or study-specific entities.…”
Section: Discussionmentioning
confidence: 99%
“…The use of big data to understand public health issues is a novel way to provide clinical and translational science awards programs insight on community priorities that lend themselves to community-engaged research approaches [71]. Our other research indicates that meaningful community engagement offers the opportunity to promote bi-directional dialogue about health research with diverse communities [71][72][73].…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, our local county health needs assessments identified mental health and obesity as top community health priorities. Our data therefore provide important baseline information for local county health departments and healthcare systems to measure the success (impact) of community-engaged mental and behavioral health promotion efforts over time [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we examined rural-urban health disparities in the prevalence of obesity and any mood disorder diagnosis over a 5-year period, in three local Minnesota counties served by our National Institutes of Health (NIH)-funded Clinical and Translational Science Award (CTSA), with different proportions of residents living in rural areas. We focused on these two health outcomes, because mental health and obesity were identified as the top two community health priorities from 2014 to 2016 in all three counties [4][5][6][7]. In addition, a survey involving a convenience sample of 418 community members statewide in Minnesota (10% rural residence) revealed that mental health and wellness (e.g., obesity and physical activity) were reported as top health needs [8].…”
Section: Introductionmentioning
confidence: 99%